2020
DOI: 10.3390/biom10081184
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Valorization of Food Marine Wastes: Microbial Productions on Peptones Obtained from Aquaculture By-Products

Abstract: Based on a biotechnological strategy, in the present work several peptones are produced from the Alcalase hydrolysis (0.1–0.2% v/w, 56–64 °C, pH 8.27–8.98, 3 h) and thermal processing (105 °C, 60 min) of wastes generated from the industrial processing of turbot, salmon, trout, seabream and seabass. These peptones were included (in the range of 2.6–11 g/L of soluble protein) as main source of organic nitrogen (protein substrates) in low-cost media for the culture of lactic acid bacteria (LAB), marine probiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…The high medium cost of the laboratory medium is mainly due to the cost for organic nitrogen sources. The medium cost for organic nitrogen sources in laboratory MRS medium, which contains 10 g L –1 beef extract, 10 g L –1 bacto peptone, and 5 g L –1 yeast extract, can be estimated at 2.71 US$ L –1 as the prices of beef extract, bacto peptone, and yeast extract are 100 US$ kg –1 , [ 27 ] 170.2 US$ kg –1[ 28 ] (calculated from 152 € kg –1 as 1€ is 1.12 US$), 1.25 US$ kg –1 , [ 29 ] respectively. In contrast, use of the CSL medium including 10 g L –1 CSL significantly reduced the cost for organic nitrogen source to 0.002 US$/L as the price of CSL is 0.2 US$/kg.…”
Section: Resultsmentioning
confidence: 99%
“…The high medium cost of the laboratory medium is mainly due to the cost for organic nitrogen sources. The medium cost for organic nitrogen sources in laboratory MRS medium, which contains 10 g L –1 beef extract, 10 g L –1 bacto peptone, and 5 g L –1 yeast extract, can be estimated at 2.71 US$ L –1 as the prices of beef extract, bacto peptone, and yeast extract are 100 US$ kg –1 , [ 27 ] 170.2 US$ kg –1[ 28 ] (calculated from 152 € kg –1 as 1€ is 1.12 US$), 1.25 US$ kg –1 , [ 29 ] respectively. In contrast, use of the CSL medium including 10 g L –1 CSL significantly reduced the cost for organic nitrogen source to 0.002 US$/L as the price of CSL is 0.2 US$/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Vázquez et al (2019a,b) described alternative processes to valorize fish discards and produce fish mince, gelatins, oils and fish protein hydrolysates to be used as aquaculture feed ingredients. Wastes generated from the industrial processing of various fish species can also be turned into peptones (watersoluble products of partial hydrolysis of proteins to be used as a liquid medium for growing bacteria) (Vázquez et al, 2020). Mussel meat is rich in protein, lipids, carbohydrates, minerals and carotenoid pigments (Grienke et al, 2014) with potential application as food/feed supplements, preservation agents and enzymes.…”
Section: Feedmentioning
confidence: 99%
“…When fishery wastes are hydrothermally treated, protein-rich peptones are obtained [93]. When these peptones were used as nitrogen sources to culture lactic acid bacteria (LAB) and marine probiotic bacteria (MPB), both of which find use in the food industry, researchers found that the production costs could be decreased by up to 75% and 98% respectively [94]. Bio-calcite-crab shells [92], oyster shells and gastropod shells-have been experimented with phosphorus adsorbents in wastewater treatment and for other value-added bio-products.…”
Section: Forestry (Silviculture)mentioning
confidence: 99%